Literacy and the politics of representation - Hamilton, Mary, 1949- (Literacies., 2012)
"Literacy is a key indicator for comparing individuals and nations in contemporary society. It is central to public debates about the nature of the public sphere, economic markets, citizenship and self-governance. Literacy and the Politics of Representation aims to uncover the constructed nature of public understandings of literacy by examining detailed examples of how literacy is represented in a range of public contexts. It looks at the ways in which knowledge about literacy is created and distributed, the location and relative power of the knowledge-makers, and examines the different semiotic resources used in such representations: images and metaphors, numerical and statistical models, and textual narratives and how they are related to one another. The book focuses on the UK from 1970 to the present, but includes a range of international comparisons and examples. In addition, exemplar chapters offer a model of analysis that can be used to deconstruct the representations of social policy issues. This book is vital reading for postgraduate students in the areas of education studies, literacy, discourse analysis and multimodality"--